Anestesi pada Pembedahan Non-Obstetri dalam Kehamilan - Apsari, Ratih Kumala Fajar; Uyun, Yusmein; Suryasaputra, Wahyu (Jurnal Komplikasi Anestesi, 2019)
Non-obstetric surgery during pregnancy posts additional concerns to anesthesiologists. The chief goals are to preserve maternal safety, maintain the pregnant state and achieve the best possible fetal outcome. The choice of anesthetic technique and the election of appropriate anesthetic drugs should be guided by indication for surgery, type, and site of the surgical procedure. Anesthesiologist must consider the effects of the disease process itself and inhibit uterine contractions and avoid preterm labour and delivery. Fetal safety requires avoidance ofpotentially dangerous drugs and assurance of continuation of adequate uteroplacental perfusion. Until date, no anesthetic drug has been shown to be clearly dangerous to the human fetus. The decision on proceeding with surgery should be made by multidisciplinary team involving anesthesiologists, obstetricians, surgeons and perinatologists. This referral aims to discuss the physiological changes of pregnant patients who will undergo non-bstetric surgery and anesthesia management for non-obstetric operations of pregnant patients.